LIPOPROTEIN(a) DAN KEBAHAYAAN SINDROM KORONER AKUT - Ira Puspitawati; Setyawati Setyawati; Dyah Wulan Anggrahini; Diah Saraswati; Aisyah Ratna Yuniarti (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
One of the risk factors of Acute Coronary Syndrome (ACS) still controversial is Lipoprotein(a). Lp(a) is one of the lipid componentshighly homologous to plasminogen and which may compete with it in the fibrinolytic pathway and has an atherogenic effect. Prior to thestudy many variaties in results have been shown. These variations are related to different population and ethnics, thus, the researcherswere triggered to investigate the role of Lp(a) on the ACS in the Indonesian population. This case control study was conducted at theSardjito General Hospital, Yogyakarta, Indonesia consisting of 40 participants in ACS as the case group and other 40 persons sufferingfrom Stable Angina Pectoris (SAP) as a control group. This study lasted from May−December 2011. The Lp(a) was measured usingturbidimetric immunoassay method while other laboratory results were obtained from the medical records. The results of this studyshowed that high Lp(a) level (more than 30 mg/dL) was the risk factor of ACS (RR=2.818, CI: 1.069–7.426). There was no difference ofthe baseline characteristics such as: the history of hypertension, diabetes mellitus, smoking, as well as in other laboratory parameters suchas: lipid profile, hemoglobine and uric acid level in the case as well as the control group. Significant differences were found in leucocytenumber, creatinine and blood glucose level. The median level of those parameters was found higher in the case group.